2024
DOI: 10.3389/fped.2024.1322783
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol: a new pharmacologic approach to counter retinopathy of prematurity progression

Francesca Pascarella,
Rosa Teresa Scaramuzzo,
Alessandro Pini
et al.

Abstract: Despite the evident progress in neonatal medicine, retinopathy of prematurity (ROP) remains a serious threat to the vision of premature infants, due to a still partial understanding of the mechanisms underlying the development of this disease and the lack of drugs capable of arresting its progression. Although ROP is a multifactorial disease, retinal vascularization is strictly dependent on oxygen concentration. The exposition of the retina of a preterm newborn, still incompletely vascularized, to an atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
0
0
0
Order By: Relevance
“…Hypoxia-induced retinal vessel growth characterizes several pathological and degenerative diseases of the retina among which retinopathy of prematurity (ROP) is characterized by abnormal vascularization as a consequence of preterm birth ( Pascarella et al, 2024 ). Among neovascular diseases of the adult, proliferative diabetic retinopathy (PDR) is the more advanced stage of DR that is characterized by thin and weak blood vessels whose bleeding can cause scar tissue leading to retinal detachment ( Kaur et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia-induced retinal vessel growth characterizes several pathological and degenerative diseases of the retina among which retinopathy of prematurity (ROP) is characterized by abnormal vascularization as a consequence of preterm birth ( Pascarella et al, 2024 ). Among neovascular diseases of the adult, proliferative diabetic retinopathy (PDR) is the more advanced stage of DR that is characterized by thin and weak blood vessels whose bleeding can cause scar tissue leading to retinal detachment ( Kaur et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…From early preclinical studies demonstrating propranolol efficacy in the OIR model, the step was short to verify whether in clinical trials, propranolol could be used as an effective therapy in infants with ROP as recently reviewed by Pascarella et al (2024) . In particular, a pilot clinical trial by Filippi et al (2013) suggested that the administration of oral propranolol (0.25 or 0.5 mg/kg every 6 h) is effective in counteracting the progression of ROP, but it can cause serious side effects.…”
Section: Introductionmentioning
confidence: 99%